Miejsce opieki we współczesnej pedagogice = Role of care in contemporary pedagogy - Muszyńska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the role of care in pedagogy and in the education of educators. The care is understood as the activity where a carer replaces a person (who, for some reason, cannot do it themselves) in their actions and life functions which enable them to live, let them stay healthy and contribute to their development. The considerations undertaken in the text lead to the conclusion about the continuous expansion of pedagogy tasks related to the issues connected with care.
Keywords: opieka; pedagogika